2005
DOI: 10.1159/000087451
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Stimulates Matrix Metalloproteinase Secretion in Human Vascular Smooth Muscle Cells via Nuclear Factor-κB and Activator Protein 1 in a Redox-Sensitive Manner

Abstract: The renin-angiotensin system contributes to atherogenesis. Matrix metalloproteinases (MMP) are thought to participate in plaque destabilization through degradation of extracellular matrix. This study tested whether angiotensin II (ANG II) induces MMP in human vascular smooth muscle cells (SMC). ANG II induced expression of MMP-1, -3, and -9, but not of MMP-2 in SMC. The expression of MMP-1, a key enzyme for collagen degradation, was studied in detail. SMC stimulated with ANG II concentration-dependently releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
91
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 68 publications
8
91
0
1
Order By: Relevance
“…Expression of MMP-1, -3, and -9 is increased in human vascular smooth muscle cells exposed to Ang II, 21 and MMP-2 expression and activity are induced by Ang II in human endothelial cells 22 and in mouse vascular smooth muscle cells. 23 Furthermore, nonhypertensive doses of Ang II were found to induce MMP-2 in young rat arteries in vivo.…”
Section: Discussionmentioning
confidence: 91%
“…Expression of MMP-1, -3, and -9 is increased in human vascular smooth muscle cells exposed to Ang II, 21 and MMP-2 expression and activity are induced by Ang II in human endothelial cells 22 and in mouse vascular smooth muscle cells. 23 Furthermore, nonhypertensive doses of Ang II were found to induce MMP-2 in young rat arteries in vivo.…”
Section: Discussionmentioning
confidence: 91%
“…Both MMP-2 and MMP-9 are induced by ROS (Luchtefeld et al 2005). Expression of another MMP, MMP-1, which is important in collagen degradation, is increased by Ang II stimulation through NF-κB and activating protein-1 (AP-1) (Browatzki et al 2005). TNFα stimulation has similar effects (Browatzki et al 2005).…”
Section: Vascular Smooth Muscle Cell Migrationmentioning
confidence: 99%
“…Expression of another MMP, MMP-1, which is important in collagen degradation, is increased by Ang II stimulation through NF-κB and activating protein-1 (AP-1) (Browatzki et al 2005). TNFα stimulation has similar effects (Browatzki et al 2005). Moreover, MMP-7, a MMP with high degradative ability, is also activated by ROS,specifically hypochloric acid (HOCl − ) (Fu et al 2001).…”
Section: Vascular Smooth Muscle Cell Migrationmentioning
confidence: 99%
“…Studies (5,9,13,29,46) have shown that ANG II induces cardiac remodeling through an upregulation of MMP activity. We examined the expression of MMPs in cardiac tissue by real-time PCR and evaluated MMP activity by zymography.…”
Section: Cardiac Expression and Activity Of Mmpsmentioning
confidence: 99%